2020
DOI: 10.1111/bjh.16745
|View full text |Cite
|
Sign up to set email alerts
|

The loss or absence of minimal residual disease of <0·1% at any time after two cycles of consolidation chemotherapy in CBFB–MYH11‐positive acute myeloid leukaemia indicates poor prognosis

Abstract: No consensus has been reached on the relationship between CBFB-MYH11 copies and prognosis. Of 1525 acute myeloid leukemia (AML) patients, 58 with CBFB-MYH11-positive AML (16/58 patients with c-kit mutation) were retrospectively analyzed with a median follow-up duration of 29.8 (range: 4.8-74.4) months. Of these, 25/58 (43.1%) patients underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT), 10 of whom had the c-kit mutation. Of the 33 patients who did not undergo allo-HSCT, recurrence in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…In addition, similar results were observed in patients with inv (16) AML. Duan et al reported in single center study that patients with CBFB-MYH11/ABL levels > 0.1% at any time after two consolidation cycles benefited more from allo-HSCT than from chemotherapy in terms of DFS (84.6% vs. 31.4%, p < 0.001) [ 16 ]. Emerging data also suggested the prognostic values of specific KIT mutations (mainly D816), especially in MRD negative status.…”
Section: Indications and Timing Of Allo-hsctmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, similar results were observed in patients with inv (16) AML. Duan et al reported in single center study that patients with CBFB-MYH11/ABL levels > 0.1% at any time after two consolidation cycles benefited more from allo-HSCT than from chemotherapy in terms of DFS (84.6% vs. 31.4%, p < 0.001) [ 16 ]. Emerging data also suggested the prognostic values of specific KIT mutations (mainly D816), especially in MRD negative status.…”
Section: Indications and Timing Of Allo-hsctmentioning
confidence: 99%
“…1. Acute myeloid leukemia AML (non-acute promyelocytic leukemia, non-APL): AML (non-APL) in CR1 Patients with intermediate- or adverse-risk AML according to ELN/NCCN risk stratification [ 9 ] Patients who achieve CR1 after > 2 cycles of therapy Patients with AML showing myelodysplasia-related changes or therapy-related myeloid changes Patients with favorable-risk AML showing any of the following features: failure to attain MMR (RUNX1-RUNX1T1 decrease> 3 log) after two consolidation cycles or loss of MMR within 6 months [ 15 , 63 ]; recurrence of a CBFB-MYH11/ABL level >0.1% at any time after two consolidation cycles [ 16 ]; D816 KIT mutation in CBF-AML [ 17 – 19 ]; FCM+ status after two consolidation CEBPAbi+ AML [ 20 ]; MRD+ status in NPM1+ AML AML (non-APL) ≥ CR2 Relapsed or refractory AML (non-APL): allo-HSCT as salvage therapy with individualized conditioning regimens APL Failure to achieve hematological CR by induction therapy Relapsed APL (molecular, cytogenetic, or hematological relapse) who remain PML-RARA-positive after reinduction …”
Section: Recommendation: Indications For and Timing Of Allo-hsctmentioning
confidence: 99%
See 2 more Smart Citations
“…The MFC MRD can be monitored in the majority of AML patients with rapid turnaround time, but an established threshold with considerably high sensitivity and reproducibility is still an unmet clinical need (7,10). Conversely, although the PCR technique is highly sensitive, its application is limited to a fraction of AML patients who harbored specific genetic aberrations suitable for MRD detection, including RUNX1-RUNX1T1, CBFB-MYH11, and PML-RARa fusions, and NPM1 mutations (5,(11)(12)(13)(14)(15)(16). Notably, the next-generation sequencing (NGS) has introduced novel molecular markers for MRD assessment, and reliable criteria for their routine application in the clinical setting are under exploration.…”
Section: Introductionmentioning
confidence: 99%